Efektivitas penggunaan gambir sebagai bahan penyamak nabati sistem C-RFP untuk pembuatan kulit jaket dari kulit domba - Sutyasmi, Sri (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
Gambier is obtained from the extraction of leaves and young twigs of Uncaria gambir, a shrub that grows in Indonesia. Gambier contains tannin by 20% to 55% so that can be used as a vegetable tanning material using the C-RFP system (C=Conditioning, R=Rapid, F=Fass (drum), P=Powder). This research aimed to determine the effectiveness of gambier as a vegetable tanning material using the C-RFP system. Pickled leather underwent a tanning process using the C-RFP system with gambier as the tanning material at various percentages, namely by 15%, 20%, and 25%, to be processed as leather for jackets. The variations of oil used to keep the leather supple were 12.5%, 15%, and 17.5%. The tanned leather was then tested in terms of its organoleptic, physical, chemical, and morphological properties. Results of the organoleptic test and most of the results of the physical test showed that leather for jackets which was tanned using a vegetable tanning material met the requirements set out by SNI 4593: 2011 (sheepskin/goatskin leather for jackets). Results of the SEM test indicated that leather for jackets which was tanned using a vegetable tanning material displayed dense and strong skin tissue, and this proves that gambier is very effective for vegetable tanning using the C-RFP system.Keywords: C-RFP, gambier, vegetable tanning, environmentally friendly.